PENGARUH PERSEPSI DAN PREFERENSI KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN PRODUK SKINCARE GLAD2GLOW - Nurul Aulia; Desi Jaelani; Dessy Herdiana; Asep Maulana (STKIP Subang, 2026)
The local skincare industry in Indonesia has experienced significant growth in line with increasing public awareness of the importance of skin care. This study aims to analyze the influence of consumer perceptions and preferences on purchasing decisions for Glad2Glow local brand skincare products. A quantitative approach was used with a causal-comparative research design, involving 100 respondents who are Glad2Glow product users residing in Karawang. Data collection was conducted through questionnaires and analyzed using multiple linear regression. The results show that both consumer perceptions and preferences have a positive and significant simultaneous and partial effect on purchasing decisions. These findings emphasize the importance of manufacturers' understanding of consumer perceptions and preferences in formulating effective marketing strategies. This study contributes to the literature on local skincare product marketing and serves as a reference for industry players to improve competitiveness through a consumer-oriented approach. Keywords: Consumer Perceptions, Consumer Preferences, Purchase Decisions, Skincare Products, Glad2Glow